Influência da profundidade do meio suporte em wetlands construídos de fluxo vertical ascendente plantados com capim vetiver - Morais, Claudir José (2019)
Constructed Wetlands (CW) are an important option on the treatment process of sanitary waste, however there is a lack of optimization around land use for the dedicated treatment area that is needed to maintain the effectiveness of any proposed treatment. The objective of this study was to evaluate if the depth of the support medium factors in the efficacy of treatment of sanitary waste through a newly built Vertical Up flow Constructed Wetland. The experiment consisted of three pilot scale constructed wetlands (CW 1, CW 2, CW 3) with a surface area of 0.22 m2 and different depths (0.45; 0.73 and 1.60 m) of the support medium which consisted of fragmented ceramic blocks. Vetiver grass seedlings were planted at a density of 23 plants m-2. The systems were evaluated through classical methodologies applied to samples of the effluent and affluent sources during 152 days (May of 2018 to October 2018): temperature measurement, pH, turbidity (NTU), dissolved oxygen (DO), redox potential (ORP), chemical oxygen demand (COD), biochemical oxygen demand (BOD), total Kjeldahl nitrogen (TKN), ammoniacal nitrogen (N Amon), nitrite (NO2-), nitrate (NO3-) and total phosphorus (P). The elemental composition of the ceramic block (Si, O, Al, Ca, C and others) associated to the irregular characteristics (grooves, granules, pores and resistance) grant beneficial characteristics to waste treatment. The pH of both the effluent and affluent was not influenced by the support medium’s depth and no significant statistical difference was observed through this parameter. During the ORP and DO monitoring, it was observed that the system had a majorly anaerobic environment but there were significant statistical differences attributed to CW 3 (p-value= 0.001) where anoxic conditions developed near the root zone. The optimal average removal efficiency of organic loads in the average removal of TKN was registered to be up to 10%, 4% for ammoniacal nitrogen and both nitrite nitrate had a better average removal on CW 3 at 41%. The removal of the phosphorus load was also higher on CW 3 (38%) where it presented significant statistical differences (p-value= 0.0043). The growth of the vetiver grass seedlings was affected by the weather and consequently had a low growth rate but at the end of the monitoring period it was found that the plants had developed well. In CW 3 the plants had a better development rate at 0.57 cm d-1 for the aerial portion and 11,5 mg d-1 for relative growth rate (RGR). The three systems where built to have similar operational characteristics aside from depth which was bigger on CW 3 (1.45 m). CW 3 showed the best global results when compared to the other two systems. With that in mind, the possibility of optimizing vertical up flow constructed wetland by increasing the ceramic block support medium’s depth was verified.